The effect of irradiation with swift heavy ions on the structural and morphological properties of beryllium oxide ceramics - A. L. Kozlovskiy; A. E. Ryskulov; V. V. Uglov; S. B. Kislitsin (Eurasian Journal of Physics and Functional Materials, 2021)
In this study the results of structural and morphological changes in Ni12+ heavy ion irradiated BeO ceramics are presented. Irradiation was carried out on DC-60 heavy ion accelerator using Ni12+ ions with an energy of 100 MeV with irradiation fluence of 1013 -1014 ions/cm2 . It has been determined that change in magnitude of atom displacements from lattice sites is exponential, which is conditioned by defect overlap regions occurrence at fluence of 1014 ions/cm2 , followed by formation of a large number of migrating defects in structure, leading to crystal structure distortion and deformation due to chemical bonds rupture. In case of defect overlap areas generation, characteristic for irradiation fluences of 5 × 1013 - 1014 ions/cm2 , amorphous inclusions formation of more than 5% was observed, that leads to thermal conductivity decrease by (15-20)%.